Algae Biomass: Characteristics and Applications Towards Algae-based Products (Developments in Applied Phycology ;, 2018)
This book is a compendium of knowledge on the useful properties of algae in the context of application as a useful component of innovative natural products. It presents all aspects of industrial applications of macroalgae biomass derived from the natural environment. Despite many interesting characteristics, algae are still regarded as undervalued raw material, therefore, present in the following chapters are not only environmental benefits arising from the development of excessive algal biomass, but also the distribution and biology of algae in natural conditions in reservoirs, methods of obtaining extracts from biomass of algae for industrial purposes. Furthermore, it also includes topics such as the use of biomass and algae extracts for the industrial purposes, in animal breeding and for agricultural purposes, as well as the economic aspects of algae biomass harvesting for industrial purposes. The book is intended for a wide audience interested in new methods of obtaining the biomass from the natural environment for industrial purposes and the manufacture of products based on bioactive substances obtained from the environment.